Worth It or Not: Effects of Price Premium on Purchase Intent of Products with Environmental Benefits - Fan, Yali; Chen, Rong; Fan, Zhuoyi (Journal of Marketing Development and Competitiveness, 2019)
Since the green products’ costs increase, how to persuade consumers to accept the premium price is central to the green marketing. This paper demonstrates that consumers infer higher perceived quality is not necessary to increase purchase intent, and perceived price fairness plays a vital role in consumers’ purchase intent on green products. These results are explained by consumers’ equity theory related to price fairness. The present study introduces a moderator of types of concern. The authors put forward some suggestions to increase consumer acceptance of green products at a premium price.